313. RISK FACTORS FOR RECURRENCE IN ADVANCED ESOPHAGEAL CANCER PATIENTS WHO RECEIVED NEOADJUVANT CHEMOTHERAPY FOLLOWED BY ESOPHAGECTOMY. (24th September 2022) - Muneoka, Yusuke; Ichikawa, Hiroshi; Usui, Kenji; Kano, Yosuke; Hirose, Yuki; Miura, Kohei; Tajima, Yosuke; Ishikawa, Takashi; Shimada, Yoshifumi; Sakata, Jun; Kosugi, Shin-ichi; Wakai, Toshifumi
Abstract: Recently, nivolumab adjuvant therapy has become a new treatment option in Japan. However, who is the good candidate of this adjuvant therapy has not been fully investigated. The aim of this study was to clarify the risk factors for recurrence in advanced esophageal cancer patients who received neoadjuvant chemotherapy (NAC) followed by esophagectomy. We retrospectively reviewed the records of 83 patients with advanced thoracic esophageal cancer who received NAC followed by esophagectomy between 2000 and 2018 (69 men and 14 women with a median age of 65 years). We evaluated relapse-free survival (RFS) and investigated the risk factors for recurrence by multivariate analysis. The regimen of NAC was Cisplatin +5-FU (CF) in 74 patients, Docetaxel + Cisplatin +5-FU in six, and CF with radiotherapy in three. The median follow-up period after esophagectomy was 53 months. The 3-year RFS rate was 58.8%. Multivariate analyses revealed ypT3–4 (Hazard ratio, 3.71; 95% confidence interval, 1.67–8.29), lymphatic invasion (3.45; 1.62–7.39), and postoperative infectious complications (2.99; 1.47–6.07) were significant risk factors for recurrence. Moreover, the prognosis of the patient group with 2 or more risk factors was significantly worse than that of the patient group with 0–1 factor (The 3-year RFS rates, 75.2% vs. 23.1%; p < 0.001). ypT3–4, lymphatic invasion, and postoperative infectious complications were significant risk factors for recurrence after esophagectomy after neoadjuvant chemotherapy. The prognosis of the patient group with 2 or more these risk factors was significantly worse, therefore, it is considered to be a candidate for nivolumab adjuvant therapy.